Structural origins of two-dimensional elastic bending in a nonaromatic organic molecular crystal. Issue 5 (19th December 2022) - Lin, Jiawei; Cao, Yuechao; Liu, Yanbo; Li, Maolin; Chen, Yifu; Zhou, Jianmin; Wu, Songgu; Gong, Junbo
Abstract : A two-dimensional elastically bent crystal based on hydrogen bonding in a nonaromatic organic molecule system was reported. Abstract : Mechanically flexible crystals are generally obtained based on weak interactions in the aromatic systems. Here, we reported the remarkable 2D elastic bending behaviors in a nonaromatic organic molecular crystal. The strong hydrogen bonding interactions are also verified to play a crucial role in the reversible bending.